PENERAPAN MODEL PEMBELAJARAN PAIR CHECK BERBASIS ETNOMATEMATIKA PADA SOAL CERITA KELAS VIII SMP AR-RISALAH - Amrina Rosada; Maria Luthfiana; Yufitri Yanto (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2023)
This study aims to determine the results of learning mathematics in class VIII SMP Ar-Risalah Lubuklinggau after using the pair check learning model based on ethnomathematics on word problems. The approach used in this research is a quantitative approach with a quasi-experimental research type. The population in this study were all class VIII of SMP Ar-Risalah Lubuklinggau for the 2022/2023 academic year. The sample taken was class VIII.A Al-Jabar with a total of 24 students. The data collection technique in this study was a test technique by giving five questions to students. The results of this study indicate that student learning outcomes experience mastery of 79% with an average value of 82.71. Based on the research using the t test with a significant level = 0.05 with the results of the hypothesis test analysis showing the final ability of students with tcount (3,180) > ttable (1.713), so it can be concluded that the mathematics learning outcomes of class VIII students at SMP Ar-Risalah for the 2022/2023 academic year after applying the model Pair Check based on Ethnomatematics on Story Problems increases.